Effect of alkaline treatment on mechanical properties of woven ramie reinforced thermoset composite - Hamdan, M. H. M.; Siregar, J. P.; Bachtiar, Dandi; Rejab, M.R.M.; Samykano, M.; Agung, E. H.; Tezara, C.*; Jaafar, J. (IOP Publishing, 2017)
Ramie fibres are one of the strongest bast fibres with valuable potential as reinforcement in a composite. In this study, the laminated composite of ramie reinforced plain woven was prepared through hand lay-up process. Prior to moulding, the ramie reinforced woven fabric was treated by soaking the fabric in 5% NaOH solution for 1 hour at room temperature. The effects of alkaline treatment on ramie reinforced woven epoxy resin and ramie reinforced woven unsaturated polyester (UPE) resin were investigated in terms of tensile, flexural, and impact properties. Five samples of both treated ramie (TR) composite and untreated ramie (UR) composite were tested and the results were averaged for comparison with one another. Based on the results obtained, the effects of 5% (w/w) concentration of alkaline solution treatment for 1 hour at room temperature are insignificant to the tensile, flexural, and impact properties. The result of UR and TR composite was compared to the composite for pure epoxy resin and UPE resin. Based on the finding, the data obtained shown no improvement in tensile properties. However, in the case of the flexural properties are enhanced except flexural modulus of the TR-epoxy composite. Impact strength only gets better when reinforcing with the untreated ramie. On overall, the TR ramie have an admirable mechanical when reinforced with the epoxy resin than UPE resin